Intolerance [videorecording (DVD)] - Griffith, D. W. (David Wark), 1875-1948; Gish, Lillian, 1893-1993; Marsh, Mae, 1895-1968; Harron, Robert, 1894-1920; Talmadge, Constance, 1898-1973 (Cohen Media Group ; Entertainment One Films [distributor], 2013)
In this cinematic milestone, director D.W. Griffith utilized enormous sets and thousands of extras in order to stage his cinematic exploration of intolerance and it's terrible effects throughout history from ancient Babylon and biblical Judea to medieval Paris and modern America.